From the standpoint of economic education, creative economic development - Stevani, Fruri; Wahjoedi, Wahjoedi; Utomo, Sugeng Hadi; Haryono, Agung (Edelweiss Applied Science and Technology, 2025)
This study aims to investigate how players in the creative economy subsectors in Bojonegoro Regency, Indonesia, are affected by their entrepreneurial expertise in terms of their creative attitudes. Data were gathered from 33 respondents who were selected through purposive sampling from a sample of 129 entrepreneurs in the creative industry, using a quantitative research methodology. Structured questionnaires and interviews were used to collect primary data, while government records provided secondary data. Multiple linear regression analysis showed that creative attitudes are positively and significantly influenced by entrepreneurial expertise. The findings highlight the importance of both formal and informal economic education in developing entrepreneurial knowledge, which in turn fosters creativity and innovation in the unorganized sector. This research supports the need for education-based approaches and knowledge transfer to sustainably build local creative economies.